Influence of chop location on boneless pork loin quality - A T Waylan; R C Johnson; John A Unruh (Kansas Agricultural Experiment Station Research Reports, 1998)
Eighty-two boneless pork loins were used to examine the effects of chop location on longissimus muscle quality. The highest quality chops came from the posterior end. They had the lowest Warner-Bratzler shear value (most tender), highest cooking yield, and a high pH and percent extractable lipid. Visual and instrumental data suggested that the most posterior chop was lighter colored and had the highest degree of marbling. Color, firmness, and marbling evaluations were similar in the central posterior section of the loin. This suggests that this section was very uniform in visual pork quality. The anterior portion of the loin was more variable in uniformity of pork quality. The most anterior chops (17 and 19 in from posterior end) were darker but softer and more watery than chops 13 and 15 in from the posterior end. Our study suggests that locations within a loin may vary in quality characteristics, color, tenderness, cooking yield, pH, and lipid (marbling).; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Pork; Longissimus muscle; Quality